Surgical Orbital Anatomy - Hu, Shirley; Colley, Patrick (Seminars in Plastic Surgery, 2019)
In this article, the anatomy of the orbit is reviewed, with a specific emphasis on surgical anatomy. A brief discussion of the ocular globe is also included. The orbits are pyramidal structures separating the upper and middle facial skeletons. The walls, apex, and base harbor several foramina and fissures as well as bony irregularities where various ligaments, muscles, and capsules attach. There are a variety of surgical approaches to the orbit, including the traditional transcutaneous and neurosurgical techniques and, more recently, minimally invasive, endoscopic approaches.
Keywords: orbital anatomy; surgical; globe